2017
DOI: 10.1093/ijnp/pyx116
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5-HT1A Receptor Stimulation in the Medial Prefrontal Cortex in the Sustained Antidepressant Effects of Ketamine

Abstract: BackgroundWe previously reported that serotonergic transmission plays an important role in antidepressant effects of ketamine. However, detailed mechanisms have not been elucidated. Among the serotonin receptor subtypes, the serotonin1A receptor in the medial prefrontal cortex has an important role in depression. Here, we investigated the role of the medial prefrontal cortex serotonin1A receptor and its signaling mechanism in the antidepressant effects of ketamine.MethodsThe role of serotonin1A receptor-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 51 publications
4
55
0
1
Order By: Relevance
“…After 3 days of recovery, each vole with normal activity received microinjections of either saline/200 nL, 0.03-μg 8-OH-DPAT/200 nL, 0.3-μg 8-OH-DPAT/200 nL, 3-μg 8-OH-DPAT/200 nL, and 0.4-μg WAY-100635/200 nL (n=8 animals per group). The 5-HT 1A R agonist 8-OH-DPAT (Sigma-Aldrich) (0.03 μg, 0.3 μg, or 3 μg in 200 nL) and the 5-HT 1A R antagonist WAY-100635 (Sigma-Aldrich) (0.4 μg in 200 nL) were dissolved in saline, and doses were chosen based on effective doses used in previous studies (Cooper et al, 2008; Fukumoto et al, 2018) with little modification, based on their effects on mandarin voles in the preliminary experiment. The speed of injection was 0.1 μL/min for 1-minute per side.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After 3 days of recovery, each vole with normal activity received microinjections of either saline/200 nL, 0.03-μg 8-OH-DPAT/200 nL, 0.3-μg 8-OH-DPAT/200 nL, 3-μg 8-OH-DPAT/200 nL, and 0.4-μg WAY-100635/200 nL (n=8 animals per group). The 5-HT 1A R agonist 8-OH-DPAT (Sigma-Aldrich) (0.03 μg, 0.3 μg, or 3 μg in 200 nL) and the 5-HT 1A R antagonist WAY-100635 (Sigma-Aldrich) (0.4 μg in 200 nL) were dissolved in saline, and doses were chosen based on effective doses used in previous studies (Cooper et al, 2008; Fukumoto et al, 2018) with little modification, based on their effects on mandarin voles in the preliminary experiment. The speed of injection was 0.1 μL/min for 1-minute per side.…”
Section: Methodsmentioning
confidence: 99%
“…The PrL is involved in regulating emotional responses (Petty et al, 1997; Broersen et al, 2000). In addition, stimulation of postsynaptic 5-HT1A heteroreceptors in the mPFC is involved in the response to antidepressants (Fukumoto et al, 2018), and suppressing the 5-HT1A heteroreceptors in the mPFC is reported to result in a depression-like phenotype (Garcia-Garcia et al, 2017). More importantly, sustained antidepressant effects are mimicked by intra-mPFC injection of a 5-HT 1A R agonist and attenuated by a 5-HT 1A R antagonist (Fukumoto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…128 Thus, even in adulthood, chronic treatment with SSRIs may influence cortical neuroplasticity via 5-HT 1A signalling. In this regard, PFC 5-HT 1A receptor signalling to phosphatidyl-inositol 3'-kinase, implicated in the acute antidepressant actions of ketamine in mice, 129 is thought to trigger synaptic remodelling. 130 The 5-HT 1A signalling mechanisms to neuroplasticity-induced behavioural changes remain incompletely understood, as reviewed recently.…”
Section: Htr1a Genotype Neurodevelopment and Neuroplasticitymentioning
confidence: 99%
“…For example, they can activate Extracellular signal-Regulated Kinase (ERK)1/2 in the hypothalamus in a Calmodulin (CaM)-dependent manner, similar to what is observed in heterologous systems (Della Rocca et al, 1999;Turner et al, 2007), whereas they inhibit ERK1/2 phosphorylation in the hippocampus (Crane et al, 2007). In contrast, an activation of the Akt pathway has been demonstrated in the hippocampus and the medial prefrontal cortex (mPFC), where an activation of the mTOR (mammalian Target Of Rapamycin) has also been described (Cowen et al, 2005;Fukumoto et al, 2018aFukumoto et al, , 2018b).…”
Section: V-canonical Signaling Events Engaged By 5-ht Receptors 5-ht1mentioning
confidence: 76%